New world, known world : shaping knowledge in early Anglo-American writing - Read, David, 1956- (University of Missouri Press, 2005)
"Examines the works of four writers from the early period of English colonization: John Smith's Generall Historie of Virginia, William Bradford's Of Plymouth Plantation, Thomas Morton's New English Canaan, and Roger Williams's A Key into the Language of America (in conjunction with The Bloudy Tenent of Persecution)"--Provided by publisher